Pharmacological Interactions on Blood Pressure Control in Arterial Hypertension, An Issue not to be Overlooked - M. Ciulla, Michele; Benfenati, Chiara; Gallazzi, Enrico; Vivona, Patizia; Meazza, Roberto; Lombardi, Federico (Cardiovascular & Haematological Disorders - Drug Targets, 2015)
Our vision of long-term treatment strategies for the prevention of target organ damage and eventually cardiovascular morbidity and mortality in essential arterial hypertension needs to be continually monitored and updated for at least three issues: 1 - the achievement of target pressure required to obtain the expected benefit needs continuous monitoring, a dose adjustment of the drug and, often, the use of combination therapies; 2 - the chronic use of certain drugs, even in combination, is associated with the possible onset of side effects; 3 - increasing of population life expectancy is inevitably associated with in an increase in drugs use with the unavoidable occurrence of adverse drug reactions, some of which can interfere with blood pressure control. These issues, still poorly studied, pose considerable problems in applying proper strategies for prevention. In this review, we will evaluate the goals of antihypertensive therapy, and its weak spots, such as the frequent side effects, that lead to poor therapy compliance. Moreover, we will review the interactions between antihypertensive and drugs used for other common disease, and their importance in not achieving the expected blood pressure reduction.
Keywords: drug interactions